Algorithm for Mining above and Below Average Utility Blogosphere Users in a Blog Network - Khare, Shashank; Choudhary, Sapna (International Journal of Computer Sciences and Engineering, 2025)
In the past few years weblogs have become a major channel for publishing content over the Internet. With the popularity of social media as a medium to communication, everyone around the world has started using weblogs as part of their communication strategy. However there remains a void of literature on mining information from blogging, and users still do not have a solid understanding of how and why people are using this tool. This is an exploratory study into the world of blogging, and it aims to add some insight as to what is going on in the blogosphere. As data mining is an important tool for gathering information in any field. Applying this tool in the field of blogosphere is somewhat we are here to discuss about. The thesis aims at gathering information related to the users and documents being published over the internet. We wish to know the documents and the users that are highly active in the blogosphere. This study of our can be conducted by mining high utility documents and users in the blogosphere. This study we have conducted on a new blogging website created by us by using ASP.Net 4.0 as the tool and then applying the code for mining and reporting of the data